(untitled) (International Journal of Innovative Technologies in Economy, 2021)
Green economy can effectively solve the issue of environmental damage happened during economic development. Meanwhile, many countries have taken the development of green economy as an economic development mode, in which the protection of ecological and environmental, and the development of economic and social could be simultaneously realized. Since the deteriorating environmental situation has seriously affected the healthy development of human society, the environmental cost management should be incorporated into the enterprise cost management research as soon as possible. This paper mainly studies the theory of natural resources and environmental system in the enterprise cost management theory, discusses the enterprise environmental cost management, confirmation and measurement under low carbon economy, provides new ideas for improving the enterprise environmental cost theory and realizing the sustainable development of economy.